Krioprezerwacja teraźniejszości? Kryzys klimatyczny i powstanie polityki zawieszenia - Lemke, Thomas (Studia Krytyczne/Critical Studies, 2022)
Scholars analyzing contemporary technologies of freezing have recently argued that “cryopolitics” represents an important extension of the classical concept of biopolitics as it operates by the principle to “make live and not let die” (Friedrich 2017; Radin and Kowal 2017). It extends temporal horizons by suspending metabolic processes and establishing a “state of a potentially reversible death” (Neumann 2006). This article advances this theoretical proposition further by exploring the dimensions of a “politics of suspension” in the light of the climate crisis. It discusses the infrastructural role of cryopreservation and cryobanking technologies in addressing biodiversity loss and the vital challenges of the Anthropocene. These technologies promise to keep future options open by reversing past extinctions in order to address the existential threats of the present. Following this imagination, de-extinction scientists and biologists dream of restoring ancient ecosystems and resurrecting extinct species as a way of responding to the climate crisis. However, this politics of suspension might also contribute to tendencies to preserve the status quo by putting on hold the political and social transformations needed to effectively respond to the climate crisis.